2008
DOI: 10.1007/bf03345590
|View full text |Cite
|
Sign up to set email alerts
|

Relative cardiac expression of growth hormone receptor and insulin-like growth factor-I mRNA in congenital heart disease

Abstract: GH may exert direct growth-promoting and metabolic actions on target tissues, but most of its effects are mediated by circulating (endocrine) or local (auto-/paracrine) IGF-I. The GH/IGF-I system has an important role in cardiac development and in maintaining the structure and function of the heart. A subgroup of children with pronounced heart defects will eventually need transplants, owing to congestive heart failure. Since the symptoms are often severe and may progress while waiting for surgery, it is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In addition, initiation and maintenance of lactation involve many hormones such as oxytocin, prolactin, growth hormone, thyroxine, adrenal corticoids, and parathyroid hormone. 30 Cardiac tissue expresses a wide variety of hormone receptors, including receptors for lactogenic hormones, 31,32 and nursing-induced changes in hormonal milieu have been reported to improve the cardiovascular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, initiation and maintenance of lactation involve many hormones such as oxytocin, prolactin, growth hormone, thyroxine, adrenal corticoids, and parathyroid hormone. 30 Cardiac tissue expresses a wide variety of hormone receptors, including receptors for lactogenic hormones, 31,32 and nursing-induced changes in hormonal milieu have been reported to improve the cardiovascular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 has a wide spectrum of physiological effects such as regulation of cardiac contractility, tissue remodelling, glucose metabolism and vasomotor activity 26 . IGF-1 has anti-apoptotic features and is present in cardiac tissue in children 27 . In young adulthood, former preterm subjects have been shown to have the highest relative mortality rates from cardiovascular-related disorders 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, GH has been shown to be involved in cardiac gene expression and collagen deposition in extracellular matrix . We have previously shown that GH receptor and IGF‐I mRNA are expressed in cardiac biopsies from children . The early increase in septal and posterior wall thickness could be influenced by direct effects of GH on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…2 We have previously shown that GH receptor and IGF-I mRNA are expressed in cardiac biopsies from children. 33 The early increase in septal and posterior wall thickness could be influenced by direct effects of GH on the heart. Interestingly, at 2 years, the effect on left ventricular diameter, normalized diastolic BP and cardiac index remained but the myocardial thickness returned to baseline values.…”
Section: Discussionmentioning
confidence: 99%